A refinement calculus for software components and architectures. - Barbosa, Marco Antonio
The complexity and ubiquity achieved by software in the present world makes it imperative, more than ever, the availability of both technologies and sound methods to drive its development. Programming 'in--the--large', component--based programming and software architecture are popular expressions which embody this concern and correspond to driving forces in current software engineering. In such a context, this paper reports on the research, which constitutes the PhD project of the author, on a formal calculus for reasoning about and transforming component--based architectures.
Keywords: Software; Software engineering; Software architectures; Theory; Refinement calculus